Alterations in bacterial metabolites, cytokines, and mucosal integrity in the caecum of broilers caused by feed additives and host-related factors - Duangnumsawang, Yada; Zentek, Jürgen; Vahjen, Wilfried; Tarradas, Joan; Goodarzi Boroojeni, Farshad (Frontiers in Physiology, 2022)
A total of 2,880 one-day-old male and female broiler chicks from two breeds, Ross308 and Cobb500 were randomly assigned to 72 pens. Broilers were offered three diets: a wheat-soybean diet without (CO), or with either a probiotic (probiotic; 2.4 x 109 CFU/kg diet of Bacillus subtilis DSM32324 and DSM32325 and B. amyloliquefaciens DSM25840) or a phytobiotic (phytobiotic; grape extract with 165 ppm procyanidin and 585 ppm polyphenol) product. The trial was conducted with a 3 × 2 × 2 factorial arrangement of diet, breed and sex in a completely randomized design and consisted of 6 replicate-pens per treatment (40 birds per pen). At day 7, 21, and 35, one chicken per pen was slaughtered for caecal sampling to quantify bacterial metabolites (digesta) as well as evaluate mRNA abundance and histomorphology (tissue). Data were subjected to ANOVA using GLM procedure to evaluate age, diet, breed and sex and their interactions. Spearman’s correlation (r) was analyzed between metabolite concentration and mRNA abundance. Overall, the concentration of short chain fatty acids increased with age, while lactate decreased from day 7 to 21 (p < 0.05). The mRNA abundance of IL-2, IL-4, IL-6, IL-8, IL-10, IL-12, IL-17α, IL-18, IFN-γ and TGF-β2 increased with age but IL-1β and TNF-α increased in abundance from day 7 to 21 and then decreased (p < 0.05). Abundance of MUC2 and CLDN5 increased after day 21 (p < 0.05). Caecal crypt depth increased with age (p < 0.05). Acidic goblet cell (GC) number peaked at day 21 (p < 0.05), while mixed GC number was not affected by age. A few impacts of breed, diet and interactions on the investigated variables showed no meaningful biological pattern. Propionate positively correlated with all cytokines investigated (r = 0.150–0.548), except TNF-α. Lactate negatively correlated with pro-inflammatory cytokines like IL-1β (r = −0.324). Aging affected caecal histomorphology, bacterial activity and genes responsible for barrier integrity and inflammatory response. This effect could be attributed to the interaction between gut microbiota and immune system as well as the direct effect of metabolites on gut histomorphology and cytokine mRNA abundance.